Single-nucleus and spatial transcriptomics reveal intestinal cellular heterogeneity, differentiation, and cell communication mechanisms in SAP-induced intestinal injury - Zhang, Lechang; Xu, Changqin; Su, Tong; Xiao, Tong; Yi, Xu; Feng, Yuemin; Wang, Jing; Zhao, Shulei (Frontiers in Immunology, 2026)
BackgroundAcute pancreatitis (AP) ranges from mild to severe, and severe disease frequently causes multi-organ damage, with intestinal injury being a major complication. The mechanisms underlying SAP-induced intestinal injury remain unclear, particularly regarding spatial cellular reorganization and functional interactions.MethodsThis study constructed a severe acute pancreatitis (SAP) rat model and employed single-nucleus RNA sequencing (snRNA-seq) and spatial transcriptome sequencing (stRNA-seq) technologies to systematically analyze the dynamic changes in intestinal cellular composition, spatial distribution, and function during SAP-induced intestinal injury.ResultssnRNA-seq identified 18 major ileal cell populations spanning epithelial, immune, stem/TA, and stromal compartments. SAP was associated with compositional remodeling characterized by downward trends in Lgr5+/Olfm4+ stem cells, TA1, goblet cells, and Paneth cells, with a reciprocal increase in enterocytes, although most proportion changes did not reach statistical significance at the animal level. Spatial transcriptomics independently captured SAP-associated tissue remodeling, including a significant reduction in Paneth cells accompanied by increases in fat cells, macrophages, goblet cells, and TA2 cells. Across epithelial lineages, SAP induced a transcriptional shift toward immune interaction with up-regulation of antigen presentation–related genes (e.g., Cd74) and down-regulation of antimicrobial/barrier effectors (e.g., Defa24, Pla2g2a, Dmbt1), which was corroborated by spatial expression patterns and spatially variable gene programs enriched for host defense responses. Pseudotime analysis suggested a redistribution of epithelial states along the stem/TA-to-enterocyte continuum, with relative depletion of early states and expansion of enterocyte-dominant states in SAP. CellChat analysis revealed globally intensified intercellular communication and nominated FN1 as the pathway with the highest differential information flow, with Lgr5+ stem cells predicted as prominent FN1 senders targeting enterocytes and smooth muscle cells. SCENIC identified reduced activity and expression of Hmga2/Myb regulons in stem compartments, and immunofluorescence showed decreasing trends in Hmga2/Myb-positive Olfm4+ and Lgr5+ stem cells in SAP.ConclusionsIntegrated single-nucleus and spatial transcriptomics reveal that SAP is accompanied by spatially organized ileal remodeling, epithelial immune-interacting rewiring, and altered neighborhood architecture, together with an ECM-centered FN1 signaling axis and attenuated Hmga2/Myb-associated regulatory programs in stem compartments. These findings provide a spatially informed cellular framework and generate testable hypotheses for mechanisms underlying impaired epithelial regeneration during SAP-associated intestinal injury.